Bahasa Inggris Bahasa Inggris: Bahasa Indonesia - Fiesta, Santhalia Cindy (The Prosecutor Law Review, 2026)
This study aims to analyze the implementation of the Civil and Administrative Affairs Division of the Attorney General’s Office of the Republic of Indonesia in providing civil legal assistance, identifying existing obstacles, and formulating optimization strategies to ensure effective public access to justice. The research employs a normative juridical method with statutory, conceptual, and case approaches. The findings reveal that although the legal foundation of the Civil and Administrative Affairs Division’s authority is strong, implementation still faces internal barriers such as the limited number of State Attorneys (JPN), lack of continuous training, and insufficient budget, as well as external barriers including low legal awareness and complex administrative procedures. Optimization efforts include institutional strengthening, professional capacity building, digitalization of legal services, and inter-agency coordination to realize inclusive and sustainable access to justice.